Toxicological impact of sodium benzoate on inflammatory cytokines, oxidative stress and biochemical markers in male Wistar rats. (4th May 2022) - Khan, Ishfaq Shafi; Dar, Khalid Bashir; Ganie, Showkat Ahmad; Ali, Md. Niamat
Abstract: Sodium benzoate is a widely used food and pharmaceutical preservative due to its antibacterial and antifungal activity. In the present study effect of different concentrations of sodium benzoate on hepatic antioxidants, inflammatory cytokines (TNF-α, IFN-γ, IL-1β and IL-6), biochemical markers and histopathology of liver was evaluated. Twenty five adult rats (aged 1–2 months) with 5 rats per group were randomly distributed into 5 groups. Group 1 rats were used as control and all groups (1–5) were provided with water and fed ad libitum . In addition to usual water and food, rats of group 2, 3, 4 and 5 were treated with 70, 200, 400 and 700 mg/kg b.wt of sodium benzoate once a day via oral gavage for 30 days. Our results showed that activity of glutathione peroxidase (GPx), catalase (CAT), glutathione-s-transferase (GST), glutathione reductase (GR) and superoxide dismutase (SOD) in rats decreased significantly when treated with 200, 400 and 700 mg/kg b.wt of sodium benzoate. Increase in the concentration of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, serum total protein, albumin, globulin, urea and creatinine was found to be dose dependent. Severe histopathological damage was observed in the hepatic tissue at higher concentrations of sodium benzoate. It was noticed that high concentrations of sodium benzoate (200, 400 and 700 mg/kg b.wt) produce significant increase in inflammatory cytokine markers (TNF-α, IFN-γ, IL-1β and IL-6) in comparison to control. Sodium benzoate at concentration of 70 mg/kg b.wt did not produce any significant changes in any of the above studied parameters.